Logística reversa no descarte de baterias automotivas no município de Araguaína –TO - Lima, Glauber Aylan Silva (Universidade Federal do Tocantins, 2024)
The ever-growing automotive trade, along with the implementation of stricter product disposal laws, highlights the growing importance of reverse logistics. Given this context, this study aims to analyze the reverse logistics process of post-consumer automotive batteries in the city of Araguaína - TO, and verify whether the process complies with the 12th principle of the Sustainable Development Goals (SDGs) established by the United Nations (UN). It is essential to emphasize that the improper disposal of automotive batteries, due to the presence of toxic substances such as lead, cadmium and mercury in high concentrations, can cause damage to human health and the environment. To achieve the proposed objective, the case study methodology was adopted. Initially, the following guiding question was formulated: how does the reverse logistics process of batteries occur at the local level in the city of Araguaína - TO.? To collect the necessary data, interviews were conducted with employees of the analyzed companies. These interviews made it possible to identify the procedures for collecting, storing and recycling batteries, in addition to understanding how these practices contribute to the return of these materials to the production cycle. The results show that reverse logistics still has a long way to go in Brazil, since there is no model easily applicable by companies, which opens up new possibilities for research in this context. In addition, the data highlight the relevance of aspects such as collection, socio-environmental responsibility, inspection, selection, storage and transport of batteries, as well as the importance of their interconnections in the reverse logistics chain of unserviceable batteries. This study contributes to the understanding of the reverse logistics process for batteries in the city of Araguaína - TO, providing insights for the improvement of existing practices and enabling the implementation of more effective measures for the sustainable return of these materials to the production cycle. In this way, the aim is to meet the 12th principle of the Sustainable Development Goals (SDG), which aims to ensure sustainable production and consumption standards. Additionally, a future research idea that could be explored is the analysis of the economic impact of implementing reverse logistics for automotive batteries, taking into account the costs and benefits for companies and society as a whole. This would provide a comprehensive view on the financial viability of this system and could contribute to the wider adoption of sustainable practices in the automotive sector.